The Relationship between Self Efficacy and Environmental Literacy in Pollution and Environmental Changes Learning Material - Rosdiana, Rani; Maknun, Djohar; Roviati, Evi (Biosfer: Jurnal Tadris Biologi, 2020)
The purposes of this research were examining students' self-efficacy in pollution and environmental change learning; assessing the level of students' environmental literacy in pollution and environmental change learning, and analyzing the relationship between self-efficacy and environmental literacy in pollution and environmental change learning. The sample was determined using the purposive sampling technique. This research was a descriptive quantitative research with a single paradigm correlation design. The data collection techniques used were tests, questionnaires, and documentation. The results showed that students’ self-efficacy was in the strong category with an average score of 73; students’ environmental literacy was in the moderate category with an average score of 60. 2. The correlational value between self-efficacy and environmental literacy was 0.572 in the moderate category. The correlational value of the two variables was in a positive direction. Good self-efficacy tends to produce good environmental literacy.